Elaboração e secagem em spray dryer de bebida probiótica formulada a partir da fermentação do suco de caju - Pereira, Ana Lucia Fernandes (2013)
The objective of this study was to develop a probiotic cashew apple juice ready to drink and in the dehydrated form through spray drying. The first stage of the study was the optimization of Lactobacillus casei NRRL B-442 cultivation in cashew apple juice, to optimize the proper inoculum amount and the fermentation time. The optimum conditions for probiotic cashew apple juice production were: initial pH 6.4, fermentation temperature of 30°C, inoculation level of 7.48 log CFU/mL (L. casei) and 16 h of fermentation process. Cashew apple juice showed to be as efficient as dairy products for L. casei growth. In a second stage, the stability of probiotic cashew apple juice stored for 42 days at 4°C was evaluated. Analyses were conducted in the non fermented cashew apple juice (control), and in the fermented juices with L. casei NRRL B-442, with 8% (w/v) of sucrose (sugar table), after fermentation, and without the addition of sugar. The viability of the probiotic bacteria, sugars and organic acids content, color, antioxidant and enzymatic activity, and sensory characteristics were evaluated during the storage. Viable cell counts increased in the probiotic cashew apple containing sucrose along the storage period. Moreover, the fermentation lead to the preservation of the ascorbic acid content, which had a less intense reduction in the fermented cashew apple juices compared to the non fermented sample. The antioxidant activity and total polyphenolic compounds of cashew apple juice had a similar trend. Browning reactions and nutritional breakdown caused by enzymes were minimized in the fermented samples during storage. In these samples, a higher reduction of the enzymatic activity of polyphenoloxidase and peroxidase activity was observed. During the storage, the increase in the chroma values indicated that yellowness was reinforced, being well accepted by consumers. The sensory attributes (aroma, flavor, acidity and color) of probiotic cashew apple juice were positively influenced by storage under refrigeration for 42 days. In the third stage of the research, the effects of dehydration by spray drying in cashew apple juice containing L. casei NRRL B-442 was assessed and the influence of storage temperature on the viability of L. casei NRRL B-442 and physical properties of the powder were evaluated during 35 days of storage. The drying agents used were: 20% (w/v) maltodextrin or 10% (w/v) maltodextrin + 10% (w/v) arabic gum. The powder of probiotic cashew apple juice showed satisfactory levels of L. casei survival, during drying. During storage, the addition of 10% (w/v) maltodextrin + 10% (w/v) arabic gum kept microbial viability within satisfactory levels when the powder was subjected to cooling at 4°C. However, greater differences in the reconstituted powder color and higher rehydration time were obtained in this condition. On the other hand, the addition of 20% (w/v) maltodextrin provided better yield. In conclusion, cashew apple juice is a good substrate for the probiotic beverage production, and the condition of drying agents 10% maltodextrin + 10% arabic gum is adequate to maintain satisfactory levels of L. casei NRRL B-442 survival for 35 days, in the powder of probiotic cashew juice stored at 4°C.